Penerapan Metode Data Mining C4.5 dalam Penentuan Kelayakan Rehabilitas Rumah Warga - Aulia Sugarda; Saifullah; Jalaluddin; Agus Perdana Windarto; Wendi Robiansyah (Journal of Computing and Informatics Research, 2022)
The purpose of the study was to find out which houses deserve to be rehabilitated in Pematang Dolok Kahean Village. The source of the data used in this research is using datasets that already exist in Pematang Dolok Kahean Village. The solution given is to classify the feasibility level of residents' houses using the C4.5 data mining method and using the Rapidminer software assistance. This method was chosen because it is one of the most widely used decision tree methods to predict a case. The results of the study stated that the system's accuracy value was 83.33% using split validation where this method produced several rules that could be used in determining the feasibility of the rehabilitation of residents' houses so that government subsidies could be channeled appropriately.